Efeito do processo UHT (Ultra High Temperature) nas características químicas, enzimáticas e sensoriais de água de coco (Cocus nucifera l.) - Sucupira, Natália Rocha (2016)
The objective of this research was to study the UHT sterilization conditions of the green coconut water, avoiding the color, physical-chemical and taste changes. The work was organized into five chapters, developed in order to achieve the stipulated goals. In chapter 1 were conducted four experiments; the first was to evaluate four different binomials time X temperature (subprocessing and processing) and check the enzymatic activity and the color changes in coconut water. The second experiment aimed to analyze the use of antioxidant additives (ascorbic acid and sodium metabisulfite) in the physico-chemical enzymatic and color characteristics of coconut water. The third experiment was to investigate the change of color and the enzymatic regeneration in processing conditions and subprocessamento over 28 days storage (28°C ± 2°C). The fourth experiment evaluated the coconut water through the analysis of the global acceptance and survey descriptors. In chapter two it is used a rotational central composite design (CCRD) 23 in order to choose UHT sterilization condition with reduced enzyme activity and color change, associated with the use of sulphite. The purpose of said section was to evaluate the effect of sterilization parameters quality of coconut water after 24 hours and after 45 days storage at room temperature (28°C ± 2°C). Chapter three aimed to evaluate the physical- chemical, enzymatic and color stability of coconut water submitted to UHT sterilization (136°C/8s) in the absence and presence of 20 mg. L-1 of sulfite, during 180 days and to perform sensory analysis and commercial sterility test. With respect to chapter four, the purpose was to perform a quantitative evaluation of the primary metabolites of coconut water sterilized by UHT in the presence or absence of additive sulfite, using NMR (Nuclear Magnetic Resonance) and chemometrics. Chapter five aimed to develop blends composed of coconut water and tropical fruit pulps and assess the impact of thermal processing (pasteurization and UHT sterilization) on the functional components and the bioaccessible content after simulated digestion in vitro. As regards the conclusions of each chapter can be seen that in chapter one, the rose coconut water in subprocessing condition does not correlate with the activity of enzymes PPO and POD, polyphenol oxidase and peroxidase, respectively; the use of ascorbic acid has a yellowish coconut water, and adopted the use of sulfite in the following chapters; there was no enzymatic reactivate during 28 days of observation, in which it was in the appearance of pink in subprocessing treatments. There was no significant difference between treatments for global acceptance of sterile coconut water. About chapter two, after 45 days the color coordinate b * was positively correlated with temperature, with a tendency to yellow. There was no optimization of the sterilization process, however, the most suitable condition is the center point (135° C/9s), associated with the use of sulphite in concentrations above 20 mg. L-1. For chapter three, it was found that the coconut water sterilized by UHT showed physico-chemical and enzymatic stability. The color coordinate a * decreased and the turbidity increased over time of 180 days. As for the sensory analysis did not reveal any statistical difference between the sterilization treatment with sulphite and without sulfite. For the commercial sterility analysis, there was growth in a mesophilic treatments. Regarding the chapter four, it is concluded that the temperature was the parameter most affected the concentrations of major compounds of coconut water: glucose, sucrose, fructose, malic acid and ethanol. It was also found that lower temperatures (110°C) associated with the use of the sulfite antioxidant additive contributing to the maintenance of these compounds. As for the chapter five, it is concluded that all treatments showed statistically significant differences between the native sample and after simulating the gastrointestinal digestion in vitro, in which only about 10% to 20% of the content of functional compounds became bioaccessible. The UHT sterilized blend exhibited higher mean values bioaccessible fraction when compared to the pasteurized blend, suggesting that the sterilization condition may be advantageous with regard to total antioxidant content which became bioaccessible following gastrointestinal digestion. The results of this study indicate that the use of UHT technology associated with sulphite use was useful in the preservation of green coconut water and minimised the browning reactions, as well as revealing positive sensory acceptance.